Amlodipine affects plasma angiotensinogen: Level: Indirect evidence - Ismail, Rosnah; Lam, Sau Kuen; Chua, Chin Teong (Faculty of Medicine, University of Malaya, 1997)
The renin-angiotensin system acts to regulate body fluid volume and blood pressure. The circulating renin substrate, angiotensinogen, secreted mainly from the liver is affected by various hormones. Calcium ions thus far, have not been reported to affect the plasma level of angiotensinogen. Nevertheless, since we have previously reported that amlodipine, a selective vascular calcium channel blocker, could raise plasma prorenin and renin activities in Malaysian hypertensive patients, the aim of the present study is therefore to investigate the effect of amlodipine onthe plasma angiotensinogen level. An open single-blind study was performed on male and female hypertensives (32 - 60 years) without other complications. Following a washout: period, the patients were prescribed amlodipine either 5 or 10 mg daily, for 2 - 3 months. Blood samples were collected before and after treatment with the obtained plasmas analysed for plasma renin concentration (PRC) and plasma renin activity (PRA) using direct and indirect renin radioimmunoassay methods, respectively. Data obtained showed that amlodipine treatment significantly (p-=-10.05) increased the PRC and the PRA of the patients. In addition, the PRA was highly correlated to the PRC before (r = 0.62, p<0.001) and after (r= 0.68, p<0.001) the amlodipine treatment. The finding that the PRA rose in parallel with the rise in PRC indicated that angiotensinogen was not limiting, and that amlodipine treatment may raise the plasma angiotensinogen level.